The nutritional status of hospital patients and healthy elderly living in the community - Corish, Clare Anne (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2000)
Protein-energy undernutrition is known to occur in patients on admission to hospital. In a prospective study of 594 sequential hospital admissions, we assessed the prevalence of undernutrition among patients on admission to two Dublin hospitals using widely accepted anthropometric criteria (McWhirter & Pennington, 1994). We observed a significantly lower prevalence of undernutrition (11 %) than reported by McWhirter & Pennington, although pre-admission weight loss, functional impairment on admission and weight loss in hospital occurred to a similar extent. Using two popular nutrition screening instruments, the Nutrition Risk Index (Veterans Affairs Total Parenteral Nutrition Cooperative Study Group, 1991) and the Nutrition Risk Score (Reilly et al. 1995), the proportion of patients at risk of nutritional deterioration was similar to that reported from other centres and was considerably higher than the level of undernutrition recorded. However, classification of the degree of nutritional risk varied depending on the screening tool used.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin